2022
DOI: 10.3390/nu14183874
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Liberalization in Tetrahydrobiopterin-Treated PKU Patients: Does It Improve Outcomes?

Abstract: Purpose: this systematic review aimed to assess the effects of dietary liberalization following tetrahydrobiopterin (BH4) treatment on anthropometric measurements, nutritional biomarkers, quality of life, bone density, mental health and psychosocial functioning, and burden of care in PKU patients. Methods: the PubMed, Cochrane, and Embase databases were searched on 7 April 2022. We included studies that reported on the aforementioned domains before and after dietary liberalization as a result of BH4 treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Adherence to sapropterin was reported to be dependent on the extent of blood Phe reduction along with the increase in Phe tolerance, furthermore improving impairments in attention and executive functions [ 6 , 54 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. However, for most patients on sapropterin, diet can only be partially normalised, which does not completely alleviate the burden of MNT [ 69 , 70 ]. Despite the progress made, researchers continue to search for new treatment modalities that can further minimise the burden of PKU management and ultimately address the unmet treatment need in the long term [ 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…Adherence to sapropterin was reported to be dependent on the extent of blood Phe reduction along with the increase in Phe tolerance, furthermore improving impairments in attention and executive functions [ 6 , 54 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. However, for most patients on sapropterin, diet can only be partially normalised, which does not completely alleviate the burden of MNT [ 69 , 70 ]. Despite the progress made, researchers continue to search for new treatment modalities that can further minimise the burden of PKU management and ultimately address the unmet treatment need in the long term [ 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our results showed no differences in BMI z-scores over 6 months, which is consistent with findings from other cohorts of sapropterin treated patients [ 18 , 21 , 40 , 41 ]. However, two systematic reviews have shown that there was a trend for higher BMI in sapropterin treated patients [ 22 , 26 ]. The reasons for the increased BMI are unknown, but authors suggest that these changes could be associated with unhealthy food choices after an increase of natural protein in the diet.…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly suggested that sapropterin treatment, by reducing dietary restrictions, may improve nutritional quality of the diet and promote growth. In parallel, it is expected to improve the quality of life and lessen the burden of care; this, in turn, is expected to have benefits on the mental health of patients and their caregivers [ 22 ]. However, very few studies have focused on the type and quality of protein given [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation